Daylighting and window design. (Chartered Institution of Building Services Engineers, 1999)
In designing windows for the provision of daylight it is important to avoid causing problems with glare, noise intrusion, summertime overheating and excessive use of energy. LG10: Daylighting and window design gives the designer a means of identifying the important factors and methods for solving some of the problems which inevitably occur. -- Provided by publisher.
"CIBSE lighting guide LG10"--Spine
Keywords: Daylighting.; Windows -- Design and construction.; Buildings -- Energy conservation.; elektronické knihy; electronic books